Integration of Function Analysis and Trimming Method: A Systematic Approach for Improving a Spinal Board Design - Zadry, Hilma; Susanti, Lusi; Uswansyaf , Gamma (LPPM Universitas Andalas, 2022)
Function analysis primarily distinguishes components in a system and explains the function interactions amongst the components' pairs. It assists designers in revealing the main problematic areas (components) and contradictions. The trimming method assists in generating a simple design; thus, it can reduce costs and the number of faults. This study integrated the function analysis and trimming method as a systematic approach to product concept design based on the problem-oriented concept. A spinal board is an evacuation device for patients with an injured spinal cord. A case study of improving a spinal board design is conducted to demonstrate the applicability of the proposed approach. The study resulted in an alternate design of spinal board with some inventions which deliver improved performance in decreasing injury, increasing comfort and safety, and satisfying the users' requirements.